Development of nanocomplex mimic‐hsa‐miR‐143‐3p loaded exosome (exo‐miR) to inhibit viability, migration and proliferation of triple‐negative breast cancer - Nilasari, Fita; Haryana, Sofia Mubarika; Nugrahaningsih, Dwi Aris Agung; Satriyo, Pamungkas Bagus (Indonesian Journal of Biotechnology, 2024)
Breast cancer represents the highest number of cancer cases in Indonesia, with triple‐negative breast cancer (TNBC) being a common subtype (10–15%). MicroRNAs play a role in cancer epigenetics and contributing as core factors to the disease. The expression of miR‐143‐3p have been found to be lower in breast cancer samples from Yogyakarta and Central Java. It is known that miR‐143‐3p functions as a tumor suppressor in breast cancer, and its overexpression corresponds with an increased survival rate. The structure of miRNA is quickly degraded, an enhanced delivery system for miRNA is required. Exosomes are indeed emerging as natural delivery agent. A new approach represents that exosomes will be transfected with mimic‐hsa‐miR‐143‐3p yield an exo‐miR. The research aimed to examine how exo‐miR affects viability, migration, and proliferation using 4T1 cell line. The Exo‐Fect‐based method was used to transfect mimic‐hsa‐miR‐143‐3p into exosomes. The MTT assay, wound healing assay, and colony formation assay were used as functional assay. The MTT assay revealed that 7.5 µL/ 250,000 particles exo‐miR obtained a lower percentage of cell viability (58%) than the control (99.7%). The wound healing assay showed that transfection of 37.5 µL/ 1,250,000 particles exo‐miR was able to suppress migration by the percentage of wound closure (67%) compared to the control (100%). Exo‐miR also had a significant (p < 0.001) effect on colony‐forming abilities, as shown by fewer colonies (32) compared to the control (132). This findings demonstrated that exo‐miR represents a promising targeted approach in cancer therapy.